ANALISIS BAURAN PEMASARAN TERHADAP PERILAKU KONSUMEN DAGING SAPI DAN IMPLIKASI STRATEGI PEMASARAN DI HYPERMART KOTA MALANG - Farida Kusuma Astuti; Karunia Setyowati Suroto; Erik Priyo Santoso (Universitas Tribhuwana Tunggadewi, 2019)
This research is attempt to bring out marketing mix that dominate the consumer behavior in purchasing beef, to know marketing factors model that recognized by consumer to purchase the beef and to know what marketing strategy implemented by Hypermart MATOS. The research conducted from May to July 2018 involving 100 respondents. A purposive sampling methods was carefully used in determining respondents. Research is conducted by gathering data from primary source that is questionnaire and secondary source directly collected from the firm. Primary data analysis processed in order to highlight factor model that considered by consumer and SWOT analysis to describe company’s condition in specifying marketing strategy. The result shows that marketing mix most considered by consumer to purchase the beef including the product it self, place and promotions influences 26,414 percent, 26,165 percent and 22,778 percent, respectively. Factor model we considered including: factor 1 : competitive price and product it self such variable X5 (flavor), X7 (color), X8 (expiration date), X11 (price changes); factor 2 : the package involving variable X1 (packaging form), X2 (the package easy to open), and X3 (packaging materials); factor 3 : display product on show case as variable X4 (product display). Each factor model has their impacts 33,474 percent, 14,948 percent and 11,413 percent, respectively. Marketing strategy growth and build consists of market penetration by selling product in lower price to market segment which is sensitive to price, product development (diversification) referred to product factor model and price comparison, packaging and displays by giving recipes information from each type of beef and market development in order to fit demography condition and beef consumer characteristics in Malang.